THE IMPACT OF SOCIAL MEDIA ON PRAGMATIC UNDERSTANDING AMONG STUDENTS AT THE UNIVERSITY OF MUHAMMADIYAH TANGERANG - PUTRA, AIDIL SYAH; DIANTI, HILMINA RAHMA; PUTRI, INTAN CAHYANI (VARIABLE RESEARCH JOURNAL, 2024)
This research explores how social media affects the pragmatic comprehension of students at the University of Muhammadiyah Tangerang (UMT). It examines how platforms like Instagram, WhatsApp, Telegram, and TikTok influence their ability to use language effectively in different social situations. By conducting a literature review and qualitative research involving interviews and questionnaires with 17 students studying English education, the study identifies that these social media platforms contribute to improving pragmatic skills through informal and diverse language interactions. The findings indicate a positive view of how social media helps in interpreting implied meanings, engaging in varied interactions, and raising awareness of socio-pragmatic norms. The research ends by recommending the incorporation of social media in language education to enhance overall learning and pragmatic competence, encouraging educational institutions to utilize these tools for more interactive and effective learning environments.